FRI0398 Sl-401, a novel targeted therapy directed to the interleukin-3 receptor (CD123), kills plasmacytoid dendritic cells from systemic sclerosispatients. (12th June 2018) - Ah Kioon, M.-D.; Lindsay, R.; Chen, J.; Gordon, J.; Spiera, R.; Barrat, F.; Brooks, C.
Abstract : Background: SL-401 is a novel biologic targeted therapy directed to the interleukin-3 receptor (CD123). SL-401 is comprised of human IL-3 recombinantly fused to a truncated diphtheria toxin (DT) payload engineered such that IL-3 replaces the native DT receptor-binding domain. In this way, the IL-3 domain of SL-401 directs the cytotoxic DT payload to cells expressing CD123. Upon internalisation, SL–401 irreversibly inhibits protein synthesis and induces apoptosis of the target cell. Plasmacytoid dendritic cells (pDCs) are immune cells that express CD123, secret IFN-α, and play a role in inflammation and disease pathogenesis observed in systemic sclerosis (SSc) patients 1, 2 . Therefore, depletion of pDCs or attenuation of pDC function may represent a novel approach to treating SSc patients. Objectives: To assess the ability of SL-401 to deplete pDCs from healthy volunteers (HV) and SSc patients ex vivo . Methods: Patients fulfilled the 2013 ACR/EULAR classification criteria for SSc 3 . PBMCs from either SSc patients or healthy volunteers (HV) were prepared using Ficoll-Paque density gradient from fresh blood. pDCs were isolated from PBMCs as previously described 4 and used to further enrich additional PBMCs. pDC-enriched PBMCs (3%–6% pDCs) were cultured at 2 × 10 5 cells per well in the presence or absence of CpG-274 (0.5 mM) to activate pDCs and then incubated with SL-401 (0.01–100 ng/ml, 0.17 pM-1.7 nM) at 37°C, 5% CO2, and 95% humidity. After 24 hour of culture, pDC survival was assessed by flow cytometry (CD14-, CD3- BDCA4 +CD123+), and supernatants were collected for cytokine quantification by a multiplexed Luminex assay. Results: CD123 expression levels on pDCs from HV and SSc donors were comparable, suggesting that targeting of pDCs in SSc can be modelled in HV. SL-401 was cytotoxic towards pDCs from both HV (n=5) and SSc donors (n=3) to a similar extent. The ED50 of SL-401 against pDCs from HV and SSc was 4.3 and 3.3 ng/ml (74.5 and 57.2 pM), respectively (figure 1). No effect was observed on B or T cells across the SL-401 dose range tested. SL-401-mediated pDC depletion was further accompanied by a significant reduction in CpG-induced IFN-α secretion. Conclusions: SL-401 is a novel CD123-targeted therapy capable of killing pDCs from both HVs and SSc patients. These data present a potentially novel approach of targeting pDCs in the treatment of SSc and warrant further investigation. A clinical trial is planned. References: [1] Ah Kioon MD, Tripodo C, Fernandez D, et al. Plasmacytoid dendritic cells promote systemic sclerosis with a key role for TLR8. Sci Transl Med. 2018Jan 10;10(423). [2] van Bon L, Affandi AJ, Broen J, et al. Proteome-wide analysis and CXCL4 as a biomarker in systemic sclerosis. N Engl J Med. 2014Jan 30;370(5):433–43. [3] van den Hoogen F, Khanna D, Fransen J, et al. 2013classification criteria for systemic sclerosis: An American College of Rheumatology/European League against rheumatism collaborative initiative. Ann Rheum Dis. 2013 Nov;72(11):1747–55. [4] Guiducci C, Ott G, Chan JH, et al. Properties regulating the nature of the plasmacytoid dendritic cell response to Toll-like receptor 9 activation. J Exp Med. 2006Aug 7;203(8):1999–2008. Disclosure of Interest: M.-D. Ah Kioon Grant/research support from: Stemline Therapeutics, Inc., R. Lindsay Shareholder of: Stemline Therapeutics, Inc., Employee of: Stemline Therapeutics, Inc., J. Chen Shareholder of: Stemline Therapeutics, Inc., Employee of: Stemline Therapeutics, Inc., J. Gordon: None declared, R. Spiera: None declared, F. Barrat Grant/research support from: Stemline Therapeutics, Inc., C. Brooks Shareholder of: Stemline Therapeutics, Inc., Employee of: Stemline Therapeutics, Inc.